2015
DOI: 10.1007/s00018-015-1966-3
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and pannexins in the immune system and lymphatic organs

Abstract: Connexin43 and pannexin1 are found in immune cells. While gap junctional communication has been demonstrated between immune cells, hemichannels have been implicated in many cellular functions. Among the functions involved as being connexin dependent and pannexin dependent are cell migration, phagocytosis, antigen presentation, T-cell reactivity and B-cell responses. Surprisingly, many of these connexin-related and pannexin-related functions are not recapitulated in in vivo models. This is leading to a reevalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 79 publications
0
41
0
Order By: Relevance
“…16 Under resting conditions, Cx43 hemichannels have a low open probability but in the presence of molecules recognizable by the innate immune system, the increased assembly and opening of hemichannels can be triggered to induce release of proinflammatory molecules and ATP. 13,16 It is likely that at least some of the cells that express Cx43 hemichannels and contribute to RPE activation of the inflammasome are resident macrophages, 12,13,71,72 further supporting that the intervention with Cx43MP is regulating inflammation. Intervention in the ischemia-reperfusion rat model using a Cx43 channel blocking mimetic peptide reduced the number of inflammatory cells in the tissue and restored retinal function.…”
Section: Discussionmentioning
confidence: 99%
“…16 Under resting conditions, Cx43 hemichannels have a low open probability but in the presence of molecules recognizable by the innate immune system, the increased assembly and opening of hemichannels can be triggered to induce release of proinflammatory molecules and ATP. 13,16 It is likely that at least some of the cells that express Cx43 hemichannels and contribute to RPE activation of the inflammasome are resident macrophages, 12,13,71,72 further supporting that the intervention with Cx43MP is regulating inflammation. Intervention in the ischemia-reperfusion rat model using a Cx43 channel blocking mimetic peptide reduced the number of inflammatory cells in the tissue and restored retinal function.…”
Section: Discussionmentioning
confidence: 99%
“…S5), however, suggesting either a very early requirement for Cx43 in LECs or their precursors, before the Lyve-1 promoter is active, or that the Cx43 −/− -specific defects were due to the absence of Cx43 from a non-LEC cell-type. Cx43 is known to be expressed by mesenchymal stem cells, which can affect lymphangiogenesis (Valiunas et al, 2004; Buttler et al, 2013; Maertens et al, 2014), as well as macrophages and lymphocytes (Glass et al, 2015), which have been implicated in pathological lymphangiogenesis (Betterman and Harvey, 2016). In addition, Cx43 expression in thymic regulatory T cell precursors enhances the production of Foxp3 + regulatory T cells (Kuczma et al 2011), a population of cells which were recently shown to modulate lymphedema and promote lymphatic vessel function (Gousopoulos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Three other genes preferentially upregulated by SLR14 have been primarily characterized as neuronal proteins (Gje1, Cbln1, and Itpr1). Further investigation of these neuronal proteins revealed homology with known effectors of immune function (connexins, complement domains, and inositol receptors, respectively), which may suggest a bone fide role for these genes in the immune response (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 95%